LA TEORIA E LA PRATICA DEL DIRITTO - De Pascale, Carla (Daimon Revista Internacional de Filosofia, 1994)
The science of Right, as a particular science, is a constant object of Fichte's interest, from the early Revolutionsschriften to the latest writing. The comparision between the main works on this subject -the Grundlage des Naturrechts and the lessons on the Rechtslehre- shows that some problems of this science (i.e. the need for the certainty of Right and the necessity of a control over the central power) continue to be of extreme importance and salience. Through the modifications of Fichte's solution to this questions, the tension between the progressive extenson of the central power prerogatives and the ideal striving of the State towards its own extinction is more and more evident.